Step-by-step cooking with spices 50 deliciously spice recipes - Friend, Sophy (Lorenz Books, 1998)
For centuries spices have been highly prized for their ability to change everyday ingredients into somet hing exotic. This book presents a selection of fifty step-by -step spicy recipes